THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE OF HOTEL MURIA SEMARANG - Arta Adi Kusuma (Jurnal Ekonomi, 2021)
From the initial survey, it is known that there are weaknesses in employee performance, which can be seen from the high level of employee absenteeism which can affect the company's performance. The problem studied is how the motivation, work environment and employee performance, is there any influence of motivation and work environment on employee performance partially or simultaneously. This study aims to determine how the motivation, work environment and employee performance of Hotel Muria Semarang, to determine the effect of motivation and work environment on the performance of Hotel Muria Semarang employees either partially or simultaneously. The conclusion is that motivation is in the good category, the work environment is in the good category, and the performance of the Muria Hotel Semarang employees is in the good category. Motivation has an influence on employee performance with a contribution of 12.04%. The work environment has an influence on employee performance with a contribution of 8.88%. Motivation and work environment together have an influence on employee performance with a contribution of 37.6%. Suggestions that can be given in this study are indicators of the need for security, namely the absence of a better future guarantee from the company. It is hoped that the need for security can be overcome, such as by having a pension fund after the work period is over or an old-age guarantee. On the indicator of social needs, namely the lack of interaction between employees Motivation and work environment together have an influence on employee performance with a contribution of 37.6%. Suggestions that can be given in this study are indicators of the need for security, namely the absence of a better future guarantee from the company. It is hoped that the need for security can be overcome, such as by having a pension fund after the work period is over or an old-age guarantee. On the indicator of social needs, namely the lack of interaction between employees Motivation and work environment together have an influence on employee performance with a contribution of 37.6%. Suggestions that can be given in this study are indicators of the need for security, namely the absence of a better future guarantee from the company. It is hoped that the need for security can be overcome, such as by having a pension fund after the work period is over or an old-age guarantee. On the indicator of social needs, namely the lack of interaction between employees